2022
DOI: 10.1021/acs.est.1c08768
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Determination of Sampling Depth for Complex Environmental Systems: Case Study with Single-Cell Raman Spectroscopy Data in EBPR Systems

Abstract: Rapid progress in various advanced analytical methods, such as single-cell technologies, enable unprecedented and deeper understanding of microbial ecology beyond the resolution of conventional approaches. A major application challenge exists in the determination of sufficient sample size without sufficient prior knowledge of the community complexity and, the need to balance between statistical power and limited time or resources. This hinders the desired standardization and wider application of these technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The spectra data were processed with the smoothing and filtering, background subtraction, baseline correction steps by the software LabSpec 6 (Detailed key parameters can be found in supporting information Text S1). The statistical sufficiency of the sampling size was recently evaluated by kernel divergence computing method which showed that an approximated sampling size of 50 or 100 spectra for full-scale EBPR systems at 5% or 2% operational phenotypic units (OPUs) cluster resolution (Li et al, 2022; Majed et al, 2012). A total of 131, 190, 197 and 209 Raman spectra of single cells were obtained finally at each sampling time.…”
Section: Methodsmentioning
confidence: 99%
“…The spectra data were processed with the smoothing and filtering, background subtraction, baseline correction steps by the software LabSpec 6 (Detailed key parameters can be found in supporting information Text S1). The statistical sufficiency of the sampling size was recently evaluated by kernel divergence computing method which showed that an approximated sampling size of 50 or 100 spectra for full-scale EBPR systems at 5% or 2% operational phenotypic units (OPUs) cluster resolution (Li et al, 2022; Majed et al, 2012). A total of 131, 190, 197 and 209 Raman spectra of single cells were obtained finally at each sampling time.…”
Section: Methodsmentioning
confidence: 99%